The Andragogical Approach for Teaching English Speaking Skill for College Students - Minatul Azmi; Fitri Pangestu Noer Anggrainy (Journal of Applied Science, Engineering, Technology, and Education, 2020)
It has been known that most the college students face problems in communicating in English, especially in non-English-speaking country. The main cause is the teacher failed in choosing the appropriate approach for students. Further, it is necessary to choose a proper approach for college students for teaching speaking skills. From a philosophical point of view, there are two sorts of teaching approaches. These are the andragogy and pedagogy approaches. Andragogy is used for adult learners, and pedagogy is used for young learners. Seen from their age, students at colleges are positively categorized into adult students. Therefore, this paper aims to investigate the implementation of andragogical approach for teaching speaking skills in the intensive English program of Maulana Malik Ibrahim State Islamic University of Malang. This is qualitative descriptive research that the data collection method is an interview. The result revealed that most the teachers in intensive English program in Maulana Malik Ibrahim State Islamic University of Malang have been applied andragogical approach for teaching speaking skill. Hence, the researcher concludes that andragogical approach is the appropriate approach for the adult learner, especially in teaching speaking skills.